Propuesta metodológica para la interpretación de la norma NTC ISO 9001:2008 en el sector de la prestación de servicios hoteleros (2009)
Nowadays there is a great demand for tourism worldwide as well as new destinations that compete with existing ones, forcing the continuous improvement of products and services offered especially by the hotels sector, which should increase the competitiveness compared to domestic and international markets. A useful tool to provide opportunities for improve ment in this area is the application of the NTC ISO 9001:2008 standard which implementation brings a certification in this sector that implies recognition and competitiveness. The methodological proposal of this study aims to provide to the hotels sector with an interpretation of the NTC ISO 9001:2008 standard so its application is carried out properly in the implementation of quality management systems (QMS).